2022
DOI: 10.1111/iwj.13880
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between items of DMIST and healing of diabetic foot ulcers

Abstract: A monitoring tool for the wound-healing process of diabetic foot ulcers (DFUs) was developed. It comprises seven domains, namely, depth, maceration, inflammation/infection, size, tissue type of the wound bed, type of wound edge, and tunnelling/undermining. It was named "DMIST" based on the initials of its domains. Although DMIST is useful for assessing wound-healing processes, the monitoring items related to wound healing remain unclear, thereby making the selection of optimal care based on the assessment diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
3
0
1
Order By: Relevance
“…Our study selected a healing time of ≤12 weeks as the primary endpoint for the cost‐effectiveness analysis. Private practice wound healing is more effective, as shown by our study's mean HbA1c of 8, 38,39 mean QOL of 0.8, 40,41 and reduction in wound size 18,42 compared to that observed in national hospitals. This can be attributed to several factors.…”
Section: Discussionsupporting
confidence: 57%
“…Our study selected a healing time of ≤12 weeks as the primary endpoint for the cost‐effectiveness analysis. Private practice wound healing is more effective, as shown by our study's mean HbA1c of 8, 38,39 mean QOL of 0.8, 40,41 and reduction in wound size 18,42 compared to that observed in national hospitals. This can be attributed to several factors.…”
Section: Discussionsupporting
confidence: 57%
“…A secondary analysis of the data produced by Arisandi et al (2016) was used to develop a new seven-domain DFU assessment scale called the DMIST tool [ 7 ], which has been found to be a reliable and valid assessment tool for DFUs [ 11 ]. Three of the seven items on the DMIST scale, namely, depth, size, and maceration, have been found to be significantly correlated to wound healing, while a comparison indicated that the most frequently occurring components were wound extension size, depth, and exudate production or maceration [ 26 ], which are important indicators when monitoring wound healing [ 27 , 28 , 29 ]. In wound care management, a total score scale is essential for assessing wound healing [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to another study, the variables of size, depth, and maceration of the DMIST tool provided the best model of healing. As they play a critical role in the inhibition of wound healing, they are extremely important factors when it comes to assessing wound healing and must be monitored at all times [ 26 ]. Another study discovered that good wound healing can be expected if the wound size and DMIST score decrease in the first four weeks [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pembalut wanita adalah alat yang digunakan oleh wanita saat menstruasi yang berfungsi untuk menyerap darah dan juga biasa digunakan pembalut sehari-hari untuk memberikan kenyamanan pada organ reproduksi wanita, yang dalam proses produksinya menggunakan pembalut pemutih salah satunya adalah klorin (Cl2) . (Nasution et al, 2015) (Tsuchiya et al, 2022). Hasil ini berbeda dengan penelitian yang dilakukan oleh Yusuf et al, (2020) yang menyatakan bahwa pembalut wanita sebagai alternatif dressing dapat menurunkan skor DFUAS yang artinya terjadi peningkatan penyembuhan luka.…”
Section: Pembahasanunclassified